Deconstructing the Ferguson effect: a multilevel mediation analysis of public scrutiny, de-policing, and crime - Capellan, Joel A. (Journal of crime and justice, 2020)
Proponents of the ‘Ferguson effect’ suggest de-policing - stemming from increased public scrutiny over the death of Michael Brown - is responsible for the recent surge in crime across the United States. While this phenomenon has been the subject of widespread speculation, the hypothesized mechanism through which public scrutiny of police impacts crime have remained unexplored. This study attempts to fill the gap by deconstructing the effects of public scrutiny on crime trends in New York City police precincts over a two-year period (2014-2015). Findings indicate partial support for the Ferguson effect. While public scrutiny predicted variations in de-policing, the results show de-policing did not predict increases in crime. Interestingly, this study finds public scrutiny had a significant positive direct effect on crime rates, suggesting it increased crime through alternative causal processes. These findings have important theoretical and policy implications for understanding the causes and prevention of crime.